2021
DOI: 10.1073/pnas.2008389118
|View full text |Cite
|
Sign up to set email alerts
|

Personal experiences bridge moral and political divides better than facts

Abstract: Both liberals and conservatives believe that using facts in political discussions helps to foster mutual respect, but 15 studies—across multiple methodologies and issues—show that these beliefs are mistaken. Political opponents respect moral beliefs more when they are supported by personal experiences, not facts. The respect-inducing power of personal experiences is revealed by survey studies across various political topics, a field study of conversations about guns, an analysis of YouTube comments from aborti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 59 publications
1
81
0
Order By: Relevance
“…We found that increased social cognitive processing was dependent on the presence of bodily harm. Consistent with that finding, recent work has shown that attempts to bridge individuals with disparate beliefs are more likely to succeed when they include stories that relate personal experiences of harm (Kubin et al, 2021). More broadly, others have noted the overlap of brain regions involved in narrative and social cognition (Yuan et al, 2018).…”
Section: Social Cognitive Processes Track Crime-type Biasmentioning
confidence: 72%
“…We found that increased social cognitive processing was dependent on the presence of bodily harm. Consistent with that finding, recent work has shown that attempts to bridge individuals with disparate beliefs are more likely to succeed when they include stories that relate personal experiences of harm (Kubin et al, 2021). More broadly, others have noted the overlap of brain regions involved in narrative and social cognition (Yuan et al, 2018).…”
Section: Social Cognitive Processes Track Crime-type Biasmentioning
confidence: 72%
“…Some suggest social media (Valenzuela et al, 2019) and traditional media (Udani et al, 2018) have no effect on political polarization. While others suggest in certain circumstances, political information can actually have a depolarizing effect on viewers (Beam et al, 2018;Kubin et al, 2021;Wojcieszak et al, 2020). These mixed results highlight our understanding of when and why media exacerbates polarization is murky, pointing to the need for assessment of the literature.…”
mentioning
confidence: 96%
“…It is now more readily recognised in the literature that stories often aim to persuade in the context of debating controversial issues and are generally successful at doing so precisely because they do not have a traditional argumentative structure (Kubin et al 2021):…”
Section: What Are Stories Evidence Of?mentioning
confidence: 99%